Proceedings from the blood and marrow transplant clinical trials network myeloma intergroup workshop on immune and cellular therapy in multiple myeloma - Holstein, Sarah A.; Asimakopoulos, Fotis; Azab, Abdel Kareem; Bianchi, Giada; Bhutani, Manisha; Crews, Leslie A.; Cupedo, Tom; Giles, Hannah; Gooding, Sarah; Hillengass, Jens; John, Lukas; Kaiser, Shari; et al. (Transplantation and cellular therapy, 2022)
The Blood and Marrow Transplant Clinical Trials Network (BMT CTN) Myeloma Intergroup conducted a workshop on Immune and Cellular Therapy in Multiple Myeloma on January 7, 2022. This workshop included presentations by basic, translational, and clinical researchers with expertise in plasma cell dyscrasias. Four main topics were discussed: platforms for myeloma disease evaluation, insights into pathophysiology, therapeutic target and resistance mechanisms, and cellular therapy for multiple myeloma. Here we provide a comprehensive summary of these workshop presentations.